Evaluation of Outcome and the Influencing Factors on the Improvement of Renal Function after Anderson-Hynes Pyeloplasty in Children - Biswas, Ipsita; Ali, Ayub; Mahato, Gajendra Nath; Ullah, Skrkmass Amanath (Dhaka Shishu (Children) Hospital Journal, 2024)
Background : Pelvi-ureteric junction (PUJ) obstruction is one of the most common causes of Hydronephrosis in pediatric population. Anderson-Hynes (A-H) pyeloplasty is the standard surgical treatment of PUJ obstruction. The pyeloplasty is considered as successful when there is decrease in APD of renal pelvis in USG and improved SRF in DTPA renogram after pyeloplasty. There are many factors that may affect the SRF. These are the age of pyeloplasty, anteroposterior diameter (APD) of renal pelvis and baseline SRF. Objective: The aim of our study was to observe the functional outcome after pyeloplasty in our setting and to find out the effect of the factors (age, APD, baseline SRF) on the postoperative SRF. Methods: This quasi-experimental study was conducted at Pediatric urology department, Bangladesh Shishu Hospital and Institute, Dhaka among the children having A-H pyeloplasty for unilateral PUJ obstruction from September 2020 to December 2021. Patients associated with other anomalies, solitary kidney and redopyeloplasty cases were excluded. Changes in APD of renal pelvis and split renal function (SRF) of the obstructed kidneys were compared with the preoperative value to evaluate the outcome of pyeloplasty at 6 month after surgery. Patients were divided into Group 1: patient with improved renal function (postoperative SRF increased >5%), Group 2: patients with stable renal function (no change or <5% change in SRF), Group 3: patients with deteriorated renal function (decreased 5% or more in postoperative SRF). The groups were compared in terms of age, APD and base line SRF. The mean follows up time of the respondents was 12 months. Results: Total 30 patients included in our study. The mean postoperative APD of renal pelvis was decreased 12.80 mm and postoperative renal SRF was increased 6.04% than preoperative SRF value. Both were statistically highly significant. 56.7% of patients had significant improvement of renal function and only 10% of them had deterioration of renal function. Remaining 33% patients had stable renal function. The relation between age category and APD of renal pelvis of the patientts and postoperative renal function status was statistically not significant (p >.05). Patients who belongs to preoperative SRF <20% and >20% -40% category had statistically significant mean changes in their SRF after surgical intervention. Conclusion: Our study reflected that APD and SRF can be used for predicting success after pediatric pyeloplasty for unilateral PUJ obstruction. The factor that may affect the outcome was low baseline SRF. DS (Child) H J 2023; 39(1): 30-35